15+(c+17)=(16+c)+17

Simple and best practice solution for 15+(c+17)=(16+c)+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15+(c+17)=(16+c)+17 equation:


Simplifying
15 + (c + 17) = (16 + c) + 17

Reorder the terms:
15 + (17 + c) = (16 + c) + 17

Remove parenthesis around (17 + c)
15 + 17 + c = (16 + c) + 17

Combine like terms: 15 + 17 = 32
32 + c = (16 + c) + 17

Remove parenthesis around (16 + c)
32 + c = 16 + c + 17

Reorder the terms:
32 + c = 16 + 17 + c

Combine like terms: 16 + 17 = 33
32 + c = 33 + c

Add '-1c' to each side of the equation.
32 + c + -1c = 33 + c + -1c

Combine like terms: c + -1c = 0
32 + 0 = 33 + c + -1c
32 = 33 + c + -1c

Combine like terms: c + -1c = 0
32 = 33 + 0
32 = 33

Solving
32 = 33

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 9(3n+1)=7(7n+5)+3 | | r/5.5=22 | | 2.25=.10n*.05n | | X+17.4=-4.7 | | 5t^2-5t=2 | | 8a+125ax^3=0 | | 5+4x-x=2x+9-x | | 10000+(1500x)=18000+(1300x) | | -(k+2)+2k=-6+3k | | cos(6x)=sin(6x) | | 5t^2-5t-2=0 | | 2(2n+2)=8(4n+1)+2 | | 41+3x=8 | | -8+5b=8(-7b-1) | | 14x+5=4(2x-1)+6x+9 | | 4+y-2y=10 | | x^2+4*x-21=0 | | 0=5x+12-3y | | 8(y+2)+y=3(y+5)-2 | | 6.4x+2=3.2-4x | | -5(t-3)+8t=5t-5 | | 6y+11=-3y+38 | | n/-57 | | -3y-12-3x=0 | | 365=0.07x+35 | | -4u=100 | | 2+(1+5)=(2+1)+ | | x+5/2=2-(x+2/7) | | X^2-18x=5 | | 0.25(x-10)=6 | | -4y-15=5y+21 | | 5x+7=-3+3x+14 |

Equations solver categories